Transparansi Keuangan Berbasis Good Governance di Pondok Pesantren Al Multazam Husnul Khotimah Kuningan Jawa Barat - Khayati, Siti Qomala (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2023)
This research addresses the lack of studies on the financial management governance of Islamic boarding schools (pondok pesantren), particularly concerning transparency. While the majority of pesantren tend to follow traditional approaches, Al Multazam Husnul Khotimah Islamic Boarding School in Kuningan, West Java, serves as an exemplary model with its effective, technologically-based, and transparent financial management. The strengths of this pesantren include the use of appropriate technology, an independent external audit team, and financial resources from educational contributions. The research focuses on general financial management with an emphasis on transparency based on good governance. The qualitative research method employs a case study approach and analysis using the Miles & Huberman model. Findings indicate improved transparency through an integrative application system, supporting financial management based on good governance principles, involving the integration of values and professional financial expertise, including stages of institutional building, application-based integrative centralization, and monitoring effectiveness as well as financial efficiency audits.